Kenya : First Review Under the Twenty-Four Month Stand-By Arrangement and the Arrangement Under the Standby Credit Facility and Requests for Waivers of Applicability, Rephasing of Disbursements, and Modification of Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Kenya. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Kenya's First Reviews Under the Twenty-Four Month Stand-by Arrangement (SBA) and the Arrangement Under the Standby Credit Facility and Requests for Waivers of Applicability, Rephasing of Disbursements, and Modification of Performance Criterion (PC). Macroeconomic developments have been broadly in line with the program, including strong growth and lower current account deficits. On fiscal policy, revenue shortfalls in FY2015/16 were more than offset by under-execution of public investment. The IMF staff recommends completion of the first reviews and supports the authorities' requests for waivers of applicability for SBA for end-December 2016 PC, rephasing of disbursements, and modification of PC.